Implementación de murales en la ciudad de latacunga para dar a conocer el graffiti como un medio de expresión comunicacional con contenidos artísticos, culturales y educativos - Chillagana Chacón, Angélica Johana (2016)
The interest of this investigation is to demostrate how the graffiti with artistic, cultural and educational contents is a sort of communicational expressionfrom young people in Latacunga canton, Cotopaxi province, likewise, we looked for the designation public sites to practice the graffities withpositive messages to the community. This research was realized in quantitative way through survey and qualitative through depth interviews, with the information from this document, we confirmed that people from Latacunga look the graffiti like vandalism, but they recognize if the authorities provide public spaces and their contens were about cultural, artistic or educational….